Relationships for moments of order statistics from a generalized exponential distribution - Saran, Jagdish; Pushkarna, Narinder (Statistica, 2000)
The single and the product moments of order statistics from a generalized exponential distribution have been obtained for all sample size and for any choice of the shape parameter ... [alpha] . These moments can then be used to derive the best linear unbiased estimators (BLUE’s) of location and scale parameters from complete as well as Type II censored samples. In addition, percentage points of order statistics are also discussed.